1994
DOI: 10.1161/01.res.75.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of potassium channel mRNA expression in atrial and ventricular muscle of rats.

Abstract: The expression of 15 different potassium channel genes in rat atrial and ventricular muscle was quantitatively compared by use of an RNase protection assay. Of these genes, only five, Kv1.2, Kv1.4, Kv1.5, Kv2.1, and Kv4.2, were expressed at significant levels in cardiac muscle. In comparisons of atrial and ventricular RNA samples, transcripts from the Kv1.2 and Kv4.2 genes showed the largest differences in relative abundance. There was an approximately twofold decrease in total Kv4 subfamily mRNA expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
203
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(218 citation statements)
references
References 48 publications
13
203
2
Order By: Relevance
“…These results are consistent with a previous study showing that I sus is significantly reduced in the left ventricular endocardium after shortterm infarction (61). The molecular correlates of I sus remains uncertain, but three candidate K ϩ channel genes (Kv1.2, Kv1.5, and Kv2.1) are expressed in the rat heart (16,51,53). In the right ventricle, RNase protection assays (data not shown) revealed that the percentage reductions in mRNA levels after MI did not reach significance for Kv1.2, (23.7 Ϯ 15.3%, n ϭ 5, P ϭ 0.19), Kv1.5 (22.4 Ϯ 11.4%, n ϭ 5, P ϭ 0.11) or Kv2.1 (27.0 Ϯ 9.8%, n ϭ 5, P ϭ 0.06) genes.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with a previous study showing that I sus is significantly reduced in the left ventricular endocardium after shortterm infarction (61). The molecular correlates of I sus remains uncertain, but three candidate K ϩ channel genes (Kv1.2, Kv1.5, and Kv2.1) are expressed in the rat heart (16,51,53). In the right ventricle, RNase protection assays (data not shown) revealed that the percentage reductions in mRNA levels after MI did not reach significance for Kv1.2, (23.7 Ϯ 15.3%, n ϭ 5, P ϭ 0.19), Kv1.5 (22.4 Ϯ 11.4%, n ϭ 5, P ϭ 0.11) or Kv2.1 (27.0 Ϯ 9.8%, n ϭ 5, P ϭ 0.06) genes.…”
Section: Resultssupporting
confidence: 92%
“…To investigate the molecular basis for the changes in I to density, we examined the expression of Kv4.2, Kv4.3, and Kv1.4␣ subunits, which represent candidate voltage-dependent K ϩ channels encoding for I tolike currents previously shown to be expressed in rat heart (16). Figure 4 shows typical Western blots for Kv4.2, Kv4.3, and Kv1.4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are >15 different potassium channel genes that have been quantitatively demonstrated to exist in rat atrial and ventricular muscles, with Kcna2, kv1.4, kv1.5, kv2.1, and kv4.2 being expressed at significant levels 7, 27. Western blot analyses of atrial and ventricular membrane proteins confirmed the presence of Kcna2 at 75 kDa in adult rat heart membranes 8.…”
Section: Discussionmentioning
confidence: 91%
“…Delayed rectifier potassium channels are important for controlling the repolarization of several ion species in the heart, and decreases in the delayed rectifier potassium current (I K ) in heart failure results in action potential (AP) prolongation, which is an important contributor to the development of ventricular arrhythmias 4, 5, 6. Kcna2, also known as Kv1.2, which is a subunit of the voltage‐gated shaker channel family, is one of the dominant ion channels in cardiac muscle and encodes I K 7, 8. The expression levels of myocardial Kcna2 are decreased in hypertrophic cardiac tissue, senescent hearts, diabetic hearts, and patients with obesity‐induced cardiomyopathy,9, 10, 11, 12 indicating that Kcna2 might be a key regulator of ventricular arrhythmias in CHF.…”
Section: Introductionmentioning
confidence: 99%